Taking sides clashing views on controversial issues in cultural anthropology - Welsch, Robert Louis 1950-; Endicott, Kirk M. (McGraw-Hill/Dushkin, 2003)
This [text] is a debate-style reader designed to introduce students to controversies in cultural anthropology. The readings, which represent the arguments of leading anthropologists and educators, reflect a variety of viewpoints, and have been selected for their liveliness and substance, their relevance to the topics included in college-level study of cultural anthropology, and because of their value in a debate framework.--Back cover.